Histopathological spectrum of ovarian tumors: an institutional perspective - Phukan, Angela; Borgogoi, Meghna; Ghosh, Shaolima (International Journal of Research in Medical Sciences, 2018)
Background: Globally ovarian tumor is one of the leading causes of cancer death among women. Ovarian tumor has varied histiogenesis, clinical behavior and malignant potential. The aims and objectives of the present study is to study the histopathological pattern and age distribution of the ovarian tumors. Methods: A total of 84 cases were studied from January 2016 to December 2016. They were reviewed and analyzed for age, histopathological findings and clinical presentations. Classification was done according to WHO histologic classification of ovarian tumors. Results: Of the 84 cases, 75% were benign, 3.6% cases were borderline and 21.4% cases were malignant. Among the histological subtypes surface epithelial tumors comprised of 66.7% followed by germ cell tumors (23.9%). Serous cystadenoma (36.9%) was the most common benign tumor followed by mature cystic teratoma (17.9%). Serous cyst adenocarcinoma (10.7%) was the most common malignant tumour. Tumors were seen over age range of 10-78 years and maximum number of cases were in the 4th to 6th decade. Younger age group primarily presented with benign tumors whereas malignant tumors were common in elderly age group. Conclusions: Surface epithelial tumors were the commonest ovarian tumor. Maximum numbers of ovarian tumors were in the age range 40-59years and malignant tumors were common in >40 years of age.